PENGELOLAAN PELABUHAN SEBAGAI SIMPUL UTAMA RANTAI LOGISTIK MARITIM - Hagassi, Rizki; Raharjo, Setyo Slamet; Santy, Ni Nyoman Parahita; Mulyatno, Muji (UNIMAR AMNI Semarang, 2025)
Ports play a strategic role as key nodes in the maritime logistics chain, supporting the smooth flow of goods, distribution efficiency, and regional connectivity. This study aims to describe port management in supporting maritime logistics systems, including operational aspects, service quality, infrastructure, and stakeholder coordination. The research employs a descriptive approach using literature review, observation, and document analysis related to port management practices. The findings indicate that effective port management is influenced by operational efficiency, service quality, logistics system integration, and the utilization of information technology. Optimizing the role of ports as maritime logistics hubs requires improved operational management, infrastructure strengthening, and synergy among government institutions, port operators, and logistics stakeholders. This study is expected to provide a comprehensive overview of the strategic role of ports in supporting national maritime logistics systems